1997
DOI: 10.1080/15216549700202101
|View full text |Cite
|
Sign up to set email alerts
|

The large ribosomal protein gene cluster of a cryptomonad plastid: Gene organization, sequence and evolutionary implications

Abstract: The complete sequence of the major ribosomal protein gene cluster of the plastid genome of the cryptomonad alga Guillardia theta (formerly Cryptomonas Φ) is presented. The ribosomal protein genes (corresponding to the SIO, spc, alpha and L13/S9 operons of E. coli are found upstream of the previously reported plastid str operon, and transcribed in the same orientation. The genes are very tightly packed with as little as two nucleotides between the rpll4 and rpl24 genes. The gene arrangement is very similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Based on nucleomorph small subunit (SSU) rRNA data, Douglas et al (1991) suggested that cryptophyte plastids probably originate from a primitive red alga, as was confirmed in other SSU rRNA analyses (Maier et al, 1991;Cavalier-Smith et al, 1994;Ragan and Gutell, 1995;Van de Peer et al, 1996a). This agrees with studies based on sequences and organization of plastid genes, which indicate a relationship between rhodophyte and chromophyte plastids (Morden et al, 1992;Bhattacharya and Medlin, 1995;Van de Peer et al, 1996a;Wang et al, 1997). It is also consistent with the fact that starch is present in the cytoplasm of red algae as well as in the periplastid space of cryptomonads (McFadden, 1993).…”
Section: Introductionsupporting
confidence: 84%
“…Based on nucleomorph small subunit (SSU) rRNA data, Douglas et al (1991) suggested that cryptophyte plastids probably originate from a primitive red alga, as was confirmed in other SSU rRNA analyses (Maier et al, 1991;Cavalier-Smith et al, 1994;Ragan and Gutell, 1995;Van de Peer et al, 1996a). This agrees with studies based on sequences and organization of plastid genes, which indicate a relationship between rhodophyte and chromophyte plastids (Morden et al, 1992;Bhattacharya and Medlin, 1995;Van de Peer et al, 1996a;Wang et al, 1997). It is also consistent with the fact that starch is present in the cytoplasm of red algae as well as in the periplastid space of cryptomonads (McFadden, 1993).…”
Section: Introductionsupporting
confidence: 84%
“…There is considerable evidence for polycistronic transcription of genes for related functions, not only from the presence of gene clusters on plastid genomes, but also from transcription studies (Douglas and Murphy 1994;Löffelhardt et al 1997;Wang et al 1997). Putative promoters similar to the canonical prokaryotic-type promoter sequences have been reported upstream of many G. theta plastid genes (Douglas et al 1990;Douglas and Turner 1991;Douglas and Murphy 1994;Wang et al 1997) and inspection of sequences upstream of polycistronic transcripts known from cyanobacteria and other plastids (see Löffelhardt et al 1997) have revealed several more putative promoters.…”
Section: Resultsmentioning
confidence: 99%
“…However, problems encountered with substitutional bias caused by the relatively high A+T content of plastid genes (Lockhart et al 1992), as well as varying mutational rates of different plastid genes or different sites within genes (Van De Peer et al 1996) and the possibility of lateral gene transfers (Delwiche and Palmer 1996), have yielded conflicting results that may not reflect the true evolution of these lineages. Comparisons of gene order, on the other hand, offer a means of determining relationships among plastids that are not affected by these phenomena (Kowallik 1989(Kowallik , 1997Wang et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O. sinensis, a diatom, is derived from a secondary endosymbiosis event (Kowallik et al 1995;Wang et al 1997), which may have caused major changes in gene content and organization compared to other members of the red lineage. A comparison of these three genomes revealed that there exist large regions of conserved order (Douglas 1998).…”
Section: Introductionmentioning
confidence: 99%